COMPARING THE EFFICACY OF INJECTABLE PLATELET-RICH FIBRIN (I-PRF) WITH PLATELET-RICH PLASMA (PRP) IN THE TREATMENT OF ANDROGENIC ALOPECIA - RANI , N; SHAHZAD , MK; HASSAN , T; HANIF , N; ULLAH , M; HUMERA , F (Biological and Clinical Sciences Research Journal, 2024)
Androgenic alopecia (AGA) is a common form of hair loss affecting both men and women worldwide. Platelet-rich fibrin (PRF) and platelet-rich plasma (PRP) have emerged as promising therapies for AGA due to their regenerative properties. Aim and Objective: This study compared the efficacy of injectable platelet-rich fibrin (I-PRF) with platelet-rich plasma (PRP) in treating androgenic alopecia to determine which treatment modality yields superior hair growth outcomes in AGA patients. Methods: This randomized controlled trial was conducted at Sheikh Zayed Hospital Rahim Yar Khan from January 2024 to July 2024. One hundred patients diagnosed with AGA were recruited and randomly assigned to the I-PRF or PRP groups. The I-PRF group received injections of injectable platelet-rich fibrin, while the PRP group received platelet-rich plasma injections. Hair growth parameters, including hair density and thickness, were assessed using standardized photography and trichoscopy at baseline and 6 months. Patient satisfaction and adverse events were also recorded. Results: The I-PRF group demonstrated superior hair growth outcomes than the PRP group. Hair density and thickness analysis revealed a significant increase in both parameters in the I-PRF group compared to baseline (p < 0.001). In contrast, the PRP group showed less pronounced improvements in hair growth parameters. Patient satisfaction rates were higher in the I-PRF group, with fewer adverse events reported compared to the PRP group. Conclusion: Injectable plat Injectable platelet-rich fibrin (I-PRF) emerges as a more effective treatment modality for androgenic alopecia than platelet-rich plasma (PRP). The superior hair growth outcomes and higher patient satisfaction rates observed in the I-PRF group highlight its potential as a promising therapeutic option for AGA patients. Further research is warranted to elucidate the underlying mechanisms and optimise the use of I-PRF in the management of AGA.